Meeting Educational Demands: Teacher and Student Voices on Language Focus Needs Analysis in English Material Design for Nursing Education - Daar, Gabriel Fredi (Lingual Journal of Language and Culture, 2024)
This qualitative study aims to explore the language focus needs (reading, grammar, vocabulary, and speaking) as input material in the design of teaching materials. The research was conducted in the nursing undergraduate program at the Catholic University of Indonesia Saint Paul Ruteng, Indonesia. Data were collected through in-depth interviews and focus group discussions (FGD) with several participants. The research participants were purposively selected based on predefined criteria, resulting in 15 participants consisting of 2 English teachers, 3 nursing lectures and 10 nursing students. Data analysis was carried out using an interactive model (Miles et al., 2014). The findings of the study indicated that language focus is one of the key aspects needed as input material in designing ESP nursing teaching materials. The speaking aspect is the ultimate goal of the material being studied, and therefore, reading, grammar, and vocabulary are necessary to support speaking proficiency. Based on the perspectives of students and teachers, simple reading materials need to be included in the teaching materials to help students improve their vocabulary mastery and learn grammar in an integrative manner. The results of this research contribute to a more comprehensive understanding of the importance of analysing language focus needs in designing ESP teaching materials from the perspectives of students and teachers.